2020
DOI: 10.1002/ange.202004361
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Based Multihelicenic Architectures

Abstract: The preparation of multihelicenic systems by conventional organic synthesis is a challenging task and under continuous development. In parallel, using complexing units grafted to or incorporated within the helicene core and taking advantage of coordination/organometallic chemistry constitutes a powerful strategy to obtain multihelicenic structures. This Minireview focuses on the state‐of‐the‐art preparation of metal‐based multihelicenic architectures such as coordination‐driven supramolecular assemblies and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In particular, the π‐conjugation on the graphenic structures can be modulated by nitrogen doping due to the lone pair of electrons provided [13] . It also allows the coordination with metals [14] or protons, [15,16] which will lead to ligands in supramolecular structures or acid‐responsive materials, respectively. For instance, it has been shown that the incorporation of pyrimidine [17] or pyridine [18] rings into the HBC skeleton not only modifies the electronic properties but also allows the modulation of their properties with pH variations.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the π‐conjugation on the graphenic structures can be modulated by nitrogen doping due to the lone pair of electrons provided [13] . It also allows the coordination with metals [14] or protons, [15,16] which will lead to ligands in supramolecular structures or acid‐responsive materials, respectively. For instance, it has been shown that the incorporation of pyrimidine [17] or pyridine [18] rings into the HBC skeleton not only modifies the electronic properties but also allows the modulation of their properties with pH variations.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, enantiopure helicenes have been extensively applied as promising chiral materials for nonlinear optics, [1f,g, 3] chiral‐induced spin selectivity, [4] chiroptical switches, [5] and circularly polarized luminescence (CPL) [2g, 6] as well as for asymmetric catalysis, [7] etc. To date, structurally diverse optically active carbohelicenes and their analogues including heterohelicenes [1g, 2d,f,g] have been synthesized in a highly enantio‐ and/or diastereoselective manner through catalytic asymmetric reactions using chiral metal‐ and organocatalysts [1c,e, 8] and stereospecific reactions of optically active starting materials with point, axial, or planar chiralities [1c,e, 9] . Among them, the axially chiral biaryl derivatives have frequently been utilized as a powerful chiral auxiliary to control the helical geometry and handedness of the resulting carbo‐ and heterohelicenes since 1972 (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%